2-digit BCD counter / Ekmal Hisham Alias and Muhamad Faiz Md. Din - Alias, Ekmal Hisham; Md. Din, Muhamad Faiz (2003)
The advancement of technology allows human to design a digital application like counter. Counter is an electric apparatus that counts. It is used to count in ascending. This project is a 2-digit BCD counter where BCD means Binary Coded Decimal. Each of us has been to places that use this device especially place that offer customer services such as bank or government agencies counter where counter are used. This project is used to count from number 00 to the maximum number of 99 and then return to number 00. With the invention of this gadget people do not have to queue They only need to get their number and wait for their turn With this device they can save time and energy. In today life, time is very important. When they already get their number, they can decide either to wait or doing something else